The Effect Of Complementary Therapy Education On The Level Of Knowledge And Wound Care In Diabetic Ulcer Patients At The AEK Parombunan Community Health Center - Piuskosmas Fau (International Journal of Health Sciences, 2026)
Background: Diabetic ulcers are a common chronic complication of diabetes mellitus and can lead to severe infection and even amputation if left untreated. Proper wound care is greatly influenced by the patient's level of Complementary knowledge​ therapies, such as the use of natural ingredients and non- pharmacological approaches are widely used used by the community, but are often not accompanied by appropriate education. Objective: This study aimed to determine the effect of complementary therapy education on the level of knowledge and practice of wound care in diabetes ulcer patients at the Aek Parombunan Community Health Center. Methods: This study used a quantitative design with a quasi-experimental one-group pretest - posttest approach. The study sample consisted of 30 diabetic ulcer patients selected using a purposive sampling technique. Data were collected using knowledge​ questionnaire and wound care observation sheets before and after the complementary therapy Education. Data analysis was performed using a paired t- test with a significance level of α = 0.05.\ Results: The study showed a significant increase in patients knowledge and quality of wound care after complementary therapy education (p < 0.05). Conclusion: Complementary therapy education significantly improved knowledge and wound care practices in diabetic ulcer patients. This education can be used as a support intervention in primary healthcare.